Editor’s Introduction - Nic Ghabhann, Niamh (Irish Journal of Arts Management and Cultural Policy, 2015)
Mapping an altered landscape, held at University College Dublin in June 2014, brought together a range of perspectives and stakeholders in the Irish cultural policy and arts management sector. This special issue of the Irish Journal of Arts Management and Cultural Policy aims to reflect this conference, and, insofar as is possible, to capture some of the key ideas and questions which were part of the day. While it does not reproduce the contributions of all of the invited speakers, six papers have been selected for publication. Given the wealth of experience and expertise of all speakers on the conference programme, the process of selection was not an easy one, and this essay, together with that written by conference organisers Pat Cooke and Kerry McCall, aims to reflect the greater diversity of voices and perspectives represented on the day.